A Machine Learning Approach for Simulating the Elevation of Pilgrim Designs in Four Holy Sites Tourism - Subhash Gupta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Pilgrimage to holy sites is a centuries-old tradition embedded with cultural, spiritual, and architectural significance. Understanding and simulating the elevation of pilgrim designs in such sacred locations is crucial for enhancing tourism experiences and managing crowd dynamics. This abstract proposes a novel machine learning approach tailored for simulating pilgrim design elevations in four significant holy sites, namely Mecca, Medina, Jerusalem, and Vatican City.The proposed methodology integrates machine learning algorithms with geospatial data analysis to predict pilgrim movement patterns and design elevations. Leveraging historical pilgrimage data, spatial analysis techniques, and deep learning models, the approach aims to forecast the flow of pilgrims within these sacred environments and simulate the spatial distribution of design elements such as tents, pathways, and facilities.Key components of the methodology include data preprocessing to harmonize heterogeneous datasets, feature engineering to extract relevant spatial and temporal attributes, and model development using advanced machine learning techniques such as recurrent neural networks (RNNs) and convolutional neural networks (CNNs). The models will be trained on historical pilgrimage data, incorporating factors such as seasonality, cultural events, and infrastructure developments.The proposed framework will facilitate the generation of predictive models capable of simulating pilgrim movements and design elevations with high spatial and temporal resolution. These simulations can aid in optimizing infrastructure planning, crowd management strategies, and resource allocation during peak pilgrimage seasons. Furthermore, the insights derived from the simulations can inform decision-makers, urban planners, and tourism authorities in enhancing the overall pilgrim experience while preserving the sanctity and heritage of these holy sites.